Classroom alcohol education activities (Journal of Parents and Teachers, 2014)
This article presents a series of activities to inform students about drugs and alcohol. In turn, there are descriptions of how to carry out activities in the classroom so that students learn to differentiate different types of drugs, as well as the difference between use and abuse, to dispel myths about alcohol, etc.
Keywords: alcohol; prevention; school; education; activity